ATTITUDE SCALE TOWARDS LEARNING AL-ISLAM AND MUHAMMADIYAHAN (AIK) FOR STUDENTS OF MUHAMMADIYAH UNIVERSITY OF NORTH SUMATRA - Fanreza, Robie; Kasduri, Mario; Lubis, Said Ahmad Sarhan; Nasution, Khairil Azmi; Daulay, Mahmud Yunus; Amini, Nur Rahmah (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Al-Islam Kemuhammadiyahan, as one of the characteristics of PTM (Muhammadiyah Higher Education), is the implementation of Islamic religious education in schools, not only developed in science but also in the formation of personality, which is developed through material from the Qur'an, creeds, morals, worship, muamalah, and muhammadiyahan. Attitudes towards AIK learning influence AIK learning achievement. This research aims to develop an attitude scale towards AIK learning. This research was carried out in 4 stages: preparation, item writing, tryout, and psychometric test. Attitude towards AIK learning is conceptualized as a pattern of behavior, anticipatory tendencies or readiness, predisposition to adapt to social situations or attitudes, and response to conditioned social stimuli consisting of cognitive, affective, and conative aspects. The initial scale of 112 items was given to 30 students at the Muhammadiyah University of North Sumatra. The final results show that this scale has a good consistency (Excellent), with a value of α = 0.938.